2005
DOI: 10.1159/000082707
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of Pelvic Floor Reeducation for Men Undergoing Radical Prostatectomy

Abstract: Introduction: Urinary incontinence after radical prostatectomy is a significant clinical problem. We evaluated the clinical usefulness of early-onset pelvic floor reeducation (EPFR) as compared with later-onset pelvic floor reeducation (LPFR) in patients undergoing radical retropubic prostatectomy. Patients and Methods: The continence status of 132 consecutive patients who underwent retropubic radical prostatectomy for clinically localized prostate cancer was assessed 1 year later by a standardized questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 31 publications
1
17
0
3
Order By: Relevance
“…A positive trend concerning the timing of the training can also be observed. Pelvic floor/sphincter training seems to be more effective the earlier it is initiated [38]. Even training sessions prior to surgery are possible and have shown positive effects [36,37,41,45].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A positive trend concerning the timing of the training can also be observed. Pelvic floor/sphincter training seems to be more effective the earlier it is initiated [38]. Even training sessions prior to surgery are possible and have shown positive effects [36,37,41,45].…”
Section: Resultsmentioning
confidence: 98%
“…Primarily, physiological and psychological parameters were assessed (see "Methods" Section). While the studies that observed patients during irradiation or ADT chose an aerobic endurance and/or resistance training program [27][28][29][30][31][32][33], the remaining 14 studies examined the effects of a pelvic floor and sphincter training in inpatients pre-and/or post-op [34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pannek and König [40] retrospectively evaluated the clinical usefulness of early (7 days after surgery) as compared with later-onset pelvic fl oor re-education (4 weeks after surgery) in 132 consecutive patients 1 year after the operation. They found no statistically signifi cant difference of pelvic fl oor re-education on continence status, time to continence, frequency or volume of urine loss, or the use of pads, noting, however, a trend for patients undergoing early pelvic fl oor re-education towards sooner continence control, higher continence rate and decreased pad use.…”
Section: Rehabilitation Therapy and Post-prostatectomy Urinary Incontmentioning
confidence: 99%
“…anticholinergics) and physiotherapeutic approaches (e.g. pelvic floor muscle training, electrical stimulation, biofeedback, lifestyle adjustment) are used to improve postoperative continence, partly with excellent results [4][5][6] . In times of increasing financial distress in general healthcare systems, a cost-effective and time-saving tool to exactly evaluate incontinence as well as the therapeutic success of different approaches is truly needed.…”
Section: Introductionmentioning
confidence: 99%